Answer:
x = -5
Step-by-step explanation:
(2/3)x - (1/2) = (1/3) + (5/6)x
we observe that the denominators are 3, 2 and 6 and the lowest common multiple between the 3 numbers is 6.
Therefore we multiply each term of the equation of the equation by 6 in order to remove the fractions:
(2/3)x - (1/2) = (1/3) + (5/6)x (multiply all terms by 6)
(6)(2/3)x - (6)(1/2) = (6)(1/3) + (6)(5/6)x (simplify)
4x - 3 = 2 + 5x (add 3 to both sides)
4x = 2 + 5x + 3
4x = 5 + 5X (subtract 5x from btoh sides)
4x - 5x = 5
-x = 5 (multiply both sides by -1)
x = -5 (answer)